Literature as Social Critique: Examining Class Struggle and Inequality in Contemporary Indonesian Fiction - Akbar Ramdani (Journal of Mandalika Social Science, 2025)
Literature serves not only as an aesthetic medium, but also as a reflection and critique of complex social realities. This article aims to examine how contemporary Indonesian fictional literary works represent class struggles and social inequality as part of the discourse of social criticism. This research uses a qualitative approach with a library research method on a number of post-reform Indonesian novels that raise the theme of poverty, marginalization, and structural inequality. The analysis was carried out by utilizing social criticism theory and literary sociology approaches to identify narratives of resistance, power, and inequality that appear in literary texts. The results of the study show that these works not only voice the socio-economic conditions of marginalized groups, but also offer a space for readers to re-reflect on the unequal social structure. Indonesian contemporary fiction writers use characters, plots, and settings as narrative strategies to raise social issues symbolically and ideologically. Thus, literature plays a role as a tool for transforming social consciousness that is able to penetrate the formal boundaries of education and mainstream media. This article recommends the need to strengthen interdisciplinary studies between literature and social sciences to better understand the relationship between texts, society, and social change in contemporary Indonesia.